Could habits hold the key to weight loss maintenance? A narrative review. Issue 5 (2nd February 2017) - Cleo, G.; Isenring, E.; Thomas, R.; Glasziou, P.
Abstract: Despite the significance placed on lifestyle interventions for obesity management, most weight loss is followed by weight regain. Psychological concepts of habitual behaviour and automaticity have been suggested as plausible explanations for this overwhelming lack of long‐term weight loss success. Interventions that focus on changing an individual's behaviour are not usually successful at changing an individual's habits because they do not incorporate the strategies required to break unhealthy habits and/or form new healthy habits. A narrative review was conducted and describes the theory behind habit formation in relation to weight regain. The review evaluated the effectiveness of using habits as tools to maintain weight loss. Three specific habit‐based weight loss programmes are described: '10 Top Tips', 'Do Something Different' and 'Transforming Your Life'. Participants in these interventions achieved significant weight loss compared to a control group or other conventional interventions. Habit‐based interventions show promising results in sustaining behaviour change. Weight loss maintenance may benefit from incorporating habit‐focused strategies and should be investigated further.